Digital Currency Adoption and Its Impact on Monetary Policy Effectiveness in Emerging Markets: A Comparative Analysis - Jatiningrum, Citrawati; Ariningrum, Hardini; Abadi, Satria; Marantika, Abshor (PT. Riset Press International, 2025)
This study examines the relationship between digital currency adoption and monetary policy effectiveness across emerging markets through a comprehensive comparative analysis of twelve countries over the period 2018-2024. Using panel data regression analysis and a mixed-methods approach, we investigate how the proliferation of digital currencies—including cryptocurrencies and central bank digital currencies (CBDCs)—affects traditional monetary policy transmission mechanisms. Our findings reveal significant heterogeneity in the impact of digital currency adoption on monetary policy effectiveness, with countries exhibiting varying degrees of policy transmission disruption. The results indicate that higher levels of digital currency adoption are associated with reduced effectiveness of conventional interest rate policies, particularly in countries with weaker institutional frameworks. However, nations implementing CBDCs demonstrate improved monetary policy transmission compared to those with predominantly decentralized cryptocurrency adoption. The study contributes to the emerging literature on digital finance and monetary policy by providing empirical evidence of the trade-offs between financial innovation and monetary policy autonomy in developing economies. These findings have significant implications for central banks in emerging markets as they navigate the digital transformation of their financial systems while maintaining monetary stability.